Avatar [videorecording (Blu-Ray)] - Cameron, James, 1954-; Landau, Jon, 1960-; Worthington, Sam, 1976-; Saldana, Zoee; Ribisi, Giovanni, 1974-; Rodriguez, Michelle; Lang, Stephen, 1952-; Moore, Joel David, 1977-; Weaver, Sigourney, 1949- (20th Century Fox, 2010)
Jake Sully is a former Marine confined to a wheelchair. But despite his broken body, Jake is still a warrior at heart. He is recruited to travel light years to the human outpost on Pandora, where a corporate consortium is mining a rare mineral that is the key to solving Earth's energy crisis. He is given a mission to infiltrate the Na'vi, who have become a major obstacle to mining the precious ore. But a beautiful Na'vi female, Neytiri, saves Jake's life, and this changes everything.